Olympia, Greece. Preliminary Results of the Study of the Building Stone Used at the Archaeological Site. Research Carried Out between September and December 2023 - de Vals, Marilou (e-Forschungsberichte des DAI, 2025)
This report presents preliminary results of an ongoing project to identify building stones at Olympia. Through a first geological investigation, 14 different kinds of stone have been identified on a macroscopic scale in the in situ remains of the monuments of the Altis. These stones are exclusively sedimentary, except for marble, which appears only twice in monumental architecture. The shelly limestone (Muschelkalk), considered to be the local stone used in almost all the monuments, in fact shows high facies variability.